2016
DOI: 10.1016/j.gheart.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pragmatically Defined High CV Risk and its Correlates in LMIC: A Report From 10 LMIC Areas in Africa, Asia, and South America

Abstract: Background Current available tools for assessing high cardiovascular risk (HCR) often require measurements not available in resource-limited settings in low- and middle-income countries (LMICs). There is a need to assess HCR using a pragmatic evidence-based approach. Objective To report the prevalence of HCR in ten LMIC areas in Africa, Asia and South America, and to investigate the profiles and correlates of HCR. Methods Cross-sectional analysis using data from the NHLBI-UHG Centers of Excellence. HCR was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The results of our study indicate that women were more likely to report having heart disease than men, which was consistent with the results reported in some low- and middle-income countries, but not in most high-income countries. 29–31 This may be a result of lower healthcare seeking by women than by men, as it has been reported that, in developing countries, men use health services more frequently than women. 32 Indeed, in a study exploring gender differences in the use of healthcare in China, there was a greater use of healthcare in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study indicate that women were more likely to report having heart disease than men, which was consistent with the results reported in some low- and middle-income countries, but not in most high-income countries. 29–31 This may be a result of lower healthcare seeking by women than by men, as it has been reported that, in developing countries, men use health services more frequently than women. 32 Indeed, in a study exploring gender differences in the use of healthcare in China, there was a greater use of healthcare in men than in women.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, approximately 20 % of diabetics in South Asian countries did not know they had diabetes. 3 This study found that the baseline weight of Asians who develop diabetes is significantly higher than that of those who do not, and the amount of weight gained is greater. The strength of the study lies in the long follow-up before the diagnosis of diabetes and comparison with those who did not develop diabetes.…”
mentioning
confidence: 68%
“…In the Western Pacific Region, the burden of rheumatic heart disease is especially concentrated in China and indigenous populations living in Australia, New Zealand, and the Pacific Island States [23]. In the Eastern Mediterranean Region, rheumatic heart disease persists in certain countries such as Egypt, Sudan, and Yemen [24].…”
Section: Introductionmentioning
confidence: 99%